Influence of the degree of compaction of a reagent powder mixture on solid-phase synthesis of lithium pentaferrite; Russian Physics Journal; Vol. 50, iss. 2 - Pritulov A. M.; Usmanov R. U.; Galtseva (Gal’tseva) O. V. Olga Valerievna; Kondratyuk А. А. Alexey Alekseevich; Bezuglov V. V.; Serbin V. I. (2007, 2007)
Title screen